Cosensitization Properties of Glutathione-Protected Au25 Cluster on Ruthenium Dye-Sensitized TiO2 Photoelectrode - Kazuya Nakata; Sho Sugawara; Wataru Kurashige; Yuichi Negishi; Morio Nagata; Satoshi Uchida; Chiaki Terashima; Takeshi Kondo; Makoto Yuasa; Akira Fujishima (International Journal of Photoenergy)
Cosensitization by glutathione-protected Au25 clusters on Ru complex, N719-sensitized TiO2 photoelectrodes is demonstrated. Glutathione-protected Au25 clusters showed no significant changes in properties after adsorption onto TiO2 particles, as confirmed by optical absorption spectroscopy, transmission electron microscopy, and laser desorption/ionization mass spectrometry. Adsorption property of the glutathione-protected Au25 clusters depends on the pH, which affects the incident photon-to-current conversion efficiency (IPCE) of the TiO2 photoelectrode containing Au25 clusters. When pH < 5, the IPCE increases with pH. Conversely, the IPCE decreases with pH when pH > 7. The IPCE of a TiO2 photoelectrode sensitized by both glutathione-protected Au25 clusters and N719 was increased compared with photoelectrodes containing either glutathione-protected Au25 clusters or N719, which suggests that glutathione-protected Au25 clusters act as a coadsorbent for N719 on TiO2 photoelectrodes. This is also supported by the results that the IPCE of N719-sensitized TiO2 photoelectrodes increased upon addition of glutathione. Furthermore, cosensitization by glutathione-protected Au25 clusters on N719-sensitized TiO2 photoelectrodes allows that wavelength of photoelectric conversion was extended to the near infrared (NIR) region. These results suggest that glutathione-protected Au25 clusters act not only as a coadsorbent to increase IPCE but also as an NIR-active sensitizer.